A new type of retropancreatic fascia hernia in the supramesocolic space preoperatively misdiagnosed as a diaphragmatic hernia: report of two cases - Yoichi Nakagawa; Hiroo Uchida; Satoshi Makita; Kazuki Yokota; Akinari Hinoki; Chiyoe Shirota; Takahisa Tainaka; Wataru Sumida; Hizuru Amano; Seiya Ogata; Aitaro Takimoto; Shunya Takada; et al. (Surgical Case Reports)
Abstract Background We encountered two cases of a new type of retroperitoneal hernia. We herein report the unique features of these cases. Case presentation Case 1: A Japanese girl was born at a gestational age of 37 weeks, weighing 2550 g. She underwent laparotomic left diaphragmatic hernia repair for a left Bochdalek hernia at the age of one day. The postoperative course was uneventful; however, chest radiography at the age of 35 days revealed bowel gas in the mediastinum, while computed tomography exhibited intestinal prolapses from the medial side of the mesh into the thoracic cavity. Reoperation was performed at the age of 77 days, showing that the defect hole was not at the diaphragm but in the absence of retropancreatic fascia, which was connected to the posterior mediastinum from the supramesocolic space. The mediastinum space was closed with a suturing spine and artificial mesh, and the defect hole in the pancreatic body was sutured. Case 2: A Japanese boy was born at a gestational age of 40 weeks, weighing 3502 g. He was diagnosed with a left diaphragmatic hernia at birth and underwent laparotomy at the age of two days. Operative findings showed no defect hole in the diaphragm, and no intestine was observed in the abdominal cavity. After close observation of the abdominal cavity, the intestine was found around the pancreatic body, and manual reduction of the intestine was performed. The defect hole existed in the absence of the retropancreatic fascia, which was connected to the extra-pleural space. The defect hole in the pancreatic body was sutured and closed with a non-absorbable thread. Conclusions We assumed that our cases were a new type of retroperitoneal hernia, which we named “retropancreatic fascia hernia”.